2015
DOI: 10.1016/j.jash.2015.03.120
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking and cardio-renal events in patients with atherosclerotic renal artery stenosis

Abstract: Cigarette smoking causes cardiovascular disease and is associated with poor kidney function in individuals with diabetes mellitus and primary kidney diseases. However, the association of smoking on patients with atherosclerotic renal artery stenosis has not been studied. The current study utilized data from the Cardiovascular Outcomes in Renal Atherosclerotic Lesions (CORAL, NCT00081731) clinical trial to evaluate the effects of smoking on the risk of cardio-renal events and kidney function in this population.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Drummond et al reported that active smoking results in clinically significant ARAS, and adverse cardiorenal events, at much younger age; clearly, there is a need for smoking cessation. 111 Overall, the optimal treatment for ARAS remains poorly defined.…”
Section: Noncardiac Ascvdmentioning
confidence: 99%
“…Drummond et al reported that active smoking results in clinically significant ARAS, and adverse cardiorenal events, at much younger age; clearly, there is a need for smoking cessation. 111 Overall, the optimal treatment for ARAS remains poorly defined.…”
Section: Noncardiac Ascvdmentioning
confidence: 99%
“…Cigarette smoking may worsen renal function in people with diabetes mellitus and primary kidney diseases [25][26][27][28]; however, the effect of cigarette smoking on renal function in patients with atherosclerotic renal artery stenosis (ARAS) is uncertain. In this context, we apply our proposed method and several other methods on a dataset from the Cardiovascular Outcomes in Renal Atherosclerotic Lesions (CORAL) clinical trial [29] to study the causal effect of cigarette smoking on renal function in patients with ARAS [30]. The CORAL study was a prospective, international, randomized clinical trial that compared medical therapy only with medical therapy plus stenting in patients with ARAS, followed from May 2005 to January 2010.…”
Section: Introductionmentioning
confidence: 99%